Efeito da kinesiotaping e da altura do banco na atividade sentado para de pé em crianças com paralisia cerebral - Santos, Adriana Neves dos (2015)
Sit-to-stand movement (STS) is usually performed in daily routine. It is commonly performed from different bench heights, which modify the biomechanical demands of the task. Therefore, STS could be challenged for subjects with neuromotor impairments, such as children with Cerebral Palsy (CP). It was found only one study that evaluated STS in different bench heights in children with CP. Therefore, we have done the first study. We aimed to verify the motor strategies utilized to perform STS from three bench heights in children with CP and their typical pairs. We found that children with CP modified their motor strategies, such as, increased posterior pelvic inclination, decreased anterior movement of the trunk, increased trunk and knee flexion during standing phase and posterior dislocation of the healthy limb; during lowered bench height. Also, they presented increased duration to perform STS e asymmetrical behavior of the lower limbs. Actually, techniques that aim to increase sensory information is been applied in children with CP, such as Kinesiotaping (KT), although there is no scientific evidence of their efficacy. It has been supposed that KT increase muscle activity. Therefore, we reviewed the literature regarding the evaluation of the effects of KT in muscle activity. We observed that KT may increase muscle activity when applied for long duration in healthy individuals and subjects with muscle impairments. However, other body functions and structures, functionality and social participation do not change when KT is applied. Between these studies we did not find one that evaluated the effects of KT in children with CP. Therefore we realized the third and fourth studies. In the third study we aimed to evaluate the effects of KT in muscle activity and the motor strategies used to perform STS from three bench heights in children with CP. We found that KT leaded to increased muscle activity of rectus femoris and changes in hip kinematics variables. However, other joints angles did not change, as well as the time to perform STS. The fourth study verified the effects of KT in knee extensor torque. We increased knee extensor torque in KT condition, especially for children with outstanding weakness.